Genomic analysis identifies TJP3 as a prognostic marker for radiotherapy and chemoradiotherapy in oral squamous cell carcinoma - Su Kyung Kuk; Jae Il Lee; Jong-Ho Lee; Ik-Jae Kwon; Kang Mi Pang (Scientific Reports)
Abstract This study analyzed somatic mutations and differentially expressed genes in primary oral squamous cell carcinoma (OSCC) tumors to identify prognostic markers for radiotherapy (RT) and concurrent chemo-radiation therapy (CCRT). We used longitudinal whole-exome sequencing (WES) data from a patient who developed radiation-induced sarcoma (RIS) after CCRT with public datasets (TCGA and GSE41613) to identify genes associated with 24-month overall survival (OS). Candidates were further refined using Cox regression for OS. Twenty-two prognostic genes were identified and validated in WES data, functioning as indicators of RT and CCRT resistance. In patients with poor outcomes within 24 months post-RT, CLTCL1, RGL3 and H3C12 showed significant prognostic value in multivariate Cox analyses, while SLC35G5, GARS1 and JPH3 were identified as prognostic markers for CCRT. Limited overlap was observed between RT and CCRT, with TJP3 being the only common gene. RNA-seq data from the GSE217645 revealed that TJP3 exhibited significantly altered expression between radiosensitive and radioresistant cell lines (p = 0.037). RT-related genes were predominantly found in primary tumors, whereas CCRT-related genes were distributed across primary tumor, inflamed granulation tissue, inflammatory myofibroblastic proliferation and RIS. These findings provide insights into molecular mechanisms underlying RT and CCRT resistance, supporting future directions in precision medicine.